SEJARAH PERKEMBANGAN KONSTITUSI DITINJAU DARI PERSPEKTIF KETATANEGARAAN INDONESIASEJAK KEMERDEKAAN, ORDA LAMA, ORDA BARU DAN ERAREFORMASI HINGGA SAAT INI - ISMAIL MZ (GANEC SWARA, 2020)
The constitution is a form of agreement of all the people of a country and this is closely related to the shape of the aspired state building. The constitution is used as the highest source of law because it is an embodiment of the social agreement of all sovereign people in a country. The 1945 Constitution as the constitution of the Indonesian state is an agreement of all the people of Indonesia which was formulated by the founders of this nation from the beginning. The 1945 Constitution is one of the shortest and simplest constitutions when compared to the constitutions of various countries in the world. The history of its making is also very short because it only contains and regulates the main things, so Sukarno at the time of the enactment of the 1945 Constitution on August 18, 1945 said that the 1945 Constitution was temporary and could later be refined in the future.During the enactment of the 1945 Constitution, Indonesian politics both during the reign of President Soekarno and Suharto were widely used to mobilize and maintain the power he possessed. Soekarno, for example, has proclaimed himself to be a President for life based on MPRS Decree No. III in 1963. While Suharto was elected repeatedly as President, he was in power for 32 years. This happened because the 1945 Constitution did not explicitly formulate the term of office of the President